Evaluasi Program Izin Mendirikan Bangunan Terhadap Kawasan Kumuh Berdasarkan Tingkat Komunitas Dan Fasilitas Di Indonesia - Nurdiawan, Raul; Savitri, Tiara Nur; Ningmas, Tri Asmara; Suparwito, Velysia Ratnawati (Fakultas Ekonomi Universitas 45 Surabaya, 2022)
The building permit (IMB) policy implemented by the government aims to reduce the incompatibility of the built area with the existing spatial plan. This policy was implemented by the government through Government Regulation Number 36 of 2005 which contained the granting of permits by the Regional Government to building owners to construct buildings. However, this policy has changed its name to Building Agreement (PBG) in 2021 through Government Regulation Number 16 of 2021. In this case, the IMB seeks to reduce the discrepancy in the area of land that is used illegally which can result in the emergence of slum settlements. This study aims to see how much change has been caused by the IMB program to reduce slum area in Indonesia by using the Difference in Difference method. This method is generally used to measure how big the impact of a policy, project, activity carried out by the government. The measurement and evaluation of these impacts aims to assess how effective a program or policy is and is based on suitability with the desired goals. The data in this study were sourced from secondary data, namely the Indonesian Family Life Survey 4 and 5 which covered 13 provinces. The results of the study conclude that the IMB program has a negative effect on the existence of slums in the model test without a covariate with a significant level of 5% or 0.018 and in the model test with a covariate with a significant level of 5% or 0.034.